Water committees in the implementation of decentralization measures in the water sector in Gaza Province, Mozambique: ownership and resistance - Alves Francisco Nhaurire; Tanya Wells-Brown; Rehana Capurchande (Aqua, 2023)
As part of the water supply services decentralization in Mozambique, water user committees play a key role to manage water supply systems. However, they struggle with sustainability issues, which affect the water access to the communities. This paper intends to understand the sustainability of water systems in Mozambique based on the sociocultural dynamics, normative and institutional framework, and the interaction of social actors involved in the community management of water systems. This is a qualitative study based on phenomenology principles whose experiences were based on field work carried out in Gaza province, Mozambique. The study revealed that community management of water supply systems in Mozambique was a policy option for decentralization of water supply management, in response to the weak capacity (resources and technicians) for this purpose. The study shows that, in practice, there has yet to be much success in achieving the objectives of the Water User Committee, as they have proven to be less effective in meeting water access needs. There are challenges affecting the sustainability of the Water User Committee, such as weak understanding of their roles, conflicts, transparency, accountability and, in turn, the sustainability of water sources. HIGHLIGHTS Understand how water committees implement the promotion of WASH in study sites in Mozambique and how the water committees promote the sustainability of WASH.; Recommend changes to water committees' guidance and policy to increase their outcomes.; Understand the different interpretations and perspectives on WASH supply and the complexities involved in the triangle of policymakers, water committees' members, and users.;